Between Invasion and Excitement: Decoding YouTube Advertising Tolerance among Lima’s Youth - Ramos, Rodrigo (2024)
This study explored the attitudes of young urban consumers (18-28 years old) in Metropolitan Lima towards advertising saturation on YouTube. Aligning with the increasing interaction between brands and consumers on social networks, and how this impacts advertising effectiveness and purchase behavior, the research applied a qualitative interpretive paradigm, using a phenomenological design. In-depth interviews were conducted to gain detailed insights into perceptions of invasive advertising and receptivity towards short ads with high emotional content and artistic quality. This phenomenological approach revealed a tendency toward a preference for advertising that resonates emotionally and is aesthetically pleasing, despite a widespread resistance to excessive ads. The findings suggest that brands could benefit from advertising strategies that emphasize personalization and emotional connection to increase acceptance among young consumers.